Peminat Radio dan Podcast Kalangan Generasi Z Saat Berkendara - Pandusaputri, Nindyo Andayaning; Mokodompit, Rachmat Bintang Ramadhan; ., Irwansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research explores the change in interest in listening to Radio rather than Podcasts and assesses what factors support the change in interest in listening. The research was conducted to understand how technological developments such as digital audio platforms, and the integration of social media platforms affect the distribution of audio content such as podcasts. The researchers analyzed how these platforms affect audience, user engagement and monetization of audio content. Explored consumer behavior, listening habits, and audience preferences especially within Generation Z in relation to radio and podcasts. Researchers studied how factors such as content type, delivery style, and speed of access influence interest in listening to podcasts and online radio stations. Explore the extent to which the availability of digital audio content such as podcasts and online radio affects listener satisfaction. Researchers studied the factors that influence content selection, suitability to audience interests and listeners' response to the content presented. The trend of commodities with different purposes coming together to produce a single, multipurpose good or service is known as technological convergence, and it is a growing phenomenon that is changing the commercial landscape. Recent technological advancements have come to the attention of all human beings. The pursuit of convergence is accelerating market transformation and the creation of innovative products and services for increasingly perceptive and discerning customers. It is from this Media Convergence that research was conducted to investigate the impact of recent technologies such as on-demand audio, streaming platforms, and podcast monetization on the radio and podcast industry as a whole.